Direct and residual effects of green and farmyard manures on wheat (Triticum aestivum L) yield in a desert plain soil, Northern State, Sudan - Ahmed, Imran A.; Hamad, Muawia E.; Mohamed, Habiballa A. (Gezira Journal of Agricultural Science; Vol 17 No 2 (2019), 2019)
This study was conducted for four successive seasons during 2007 to 2011 in a desert plain soil to assess the direct and residual effects of green and farmyard manures on wheat yield components and total yield. Treatments consisted of green manure produced from green gram ( Vigna radiate )  with two seed rates (0 kg ha -1 and 12 kg ha -1 ), and farmyard manure with two levels (0 ton ha -1 and 10 ton ha -1 )  arranged in a split plot design with three replicates. For the study of the residual effects of green and farmyard  manures the treatments were fixed in the same plots of the first application of the manures, and land preparation was done manually lest to disturb the soil. The results showed that each of the investigated manures and their residuals significantly increased number of seeds per spike, 1000-seed weight, biological yield, and grain yield. According to their effectiveness in improving the yield components and increasing the yield of wheat and considering the direct effects, the interaction of green and farmyard manures came first followed by the farmyard manure and lastly the green manure treatment. The residues of the green manure treatment on the other hand produced higher yield than that of the  residues of the farmyard manure. The results also showed that the grain yield of wheat resulting from residual effects in the first year  was higher than that resulting from the primary application of manures. The residual effects in the second year resulted in lower grain yield than that of the first application of manures. It is recommended to apply organic manure every two years  to enhance the soil properties and productivity of the desert plain soil in northern Sudan.